Response of avian and mammal seed dispersal networks, to human induced forest edges in a sub-humid forest - Chaves, Patrícia Alexandra Pereira (2018)
Tese de mestrado, Biologia da Conservação, Universidade de Lisboa, Faculdade de Ciências, 2018